P I – 1–7 Effects of air pollution and physical activity on blood pressure. (18th March 2018) - Avila-Palencia, Ione; Laeremans, Michelle; Carrasco-Turigas, Glòria; Dons, Evi; Cole-Hunter, Tom; Standaert, Arnout; Anaya-Boig, Esther; Götschi, Thomas; Hoffmann, Barbara; Panis, Luc Int; Nazelle, Audrey de; Nieuwenhuijsen, Mark J
Abstract : Background/aim: The increased inhalation rate during physical activity in urban environments may result in increased inhaled dose of traffic-related air pollutants. Short-term exposure to traffic-related air pollutants has been associated with increasing blood pressure. The current study assesses the main effects and interaction effects of traffic-related air pollution and physical activity on blood pressure. Methods: A panel study was performed in three European cities (Antwerp, Barcelona, and London) with 122 healthy adults (approx. 40 participants/city) who completed 7 day measurement periods in winter, summer, and mid-season, between February 2015 and March 2016. The participants wore sensors to measure exposure to black carbon (marker of traffic-related air pollution) and physical activity levels. Blood pressure was measured three times during each measurement period. Participants also completed a questionnaire about their personal characteristics and lifestyle behaviours. Multilevel regression models will be used to assess associations and interaction effects. All models will be adjusted by potential confounders. Results: (ongoing analyses): Participants had a median (IQR) moderate-to-vigorous physical activity of 71 (49–111) min/day measured by an accelerometer. Mean black carbon exposure over all sample in coinciding time periods was 1636±673 ng/m³. The mean black carbon exposure increased with higher levels of physical activity. In initial analyses we find associations between the two exposures (black carbon and physical activity) and blood pressure. We also expect to find that physical activity levels moderates the negative effects of black carbon exposure on blood pressure. Conclusion: We hypothesise that the cardiovascular effects from traffic-related air pollution exposure could be attenuated by physical activity levels.